2015
DOI: 10.1038/eye.2015.96
|View full text |Cite
|
Sign up to set email alerts
|

The association of vitamin D deficiency with tear break-up time and Schirmer testing in non-Sjögren dry eye

Abstract: Purpose To investigate the effect of vitamin D deficiency on tear break-up time (TBUT) and Schirmer test scores and to assess their relationship in non-Sjögren dry-eye patients. Methods Thirty-four patients with serum vitamin D deficiency and 21 control subjects with normal vitamin D levels were included in this study. The TBUT and Schirmer-1 test without topical anesthesia were performed to all patients. Results The mean TBUT were 5.18 ± 2.15 and 7.36 ± 3.10 s and Schirmer scores were 12.18 ± 6.44 and 18.57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 20 publications
6
49
0
1
Order By: Relevance
“…9 Vitamin D exhibits antiinflammatory and immunoregulatory properties, and a deficiency can result in DED. 10 Because vitamin D inhibits the release of nitric oxide, a painrelated neurotransmitter, it has been shown to decrease ocular discomfort. 11 Vitamin D and its agonists have also been found to inhibit maturation and induce tolerance in dendritic cells resulting in the arrest of inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…9 Vitamin D exhibits antiinflammatory and immunoregulatory properties, and a deficiency can result in DED. 10 Because vitamin D inhibits the release of nitric oxide, a painrelated neurotransmitter, it has been shown to decrease ocular discomfort. 11 Vitamin D and its agonists have also been found to inhibit maturation and induce tolerance in dendritic cells resulting in the arrest of inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence regarding 25-hydroxyvitamin D status in ocular surface diseases such as allergic conjunctivitis and dry eye [13, 14, 20]. However, there has been some rather contradicting observations with regards to 25-hydroxyvitamin D and dry eye [15, 21].…”
Section: Discussionmentioning
confidence: 99%
“…When observing participant in accordance with dry eye severity, it showed that people with moderate and sever dry eye were more likely to be vitamin D insufficient. A recent study reported that in their optimal vitamin D (81.8688 ± 21.77) participants, there was 15% exhibiting dry eye symptoms, while dry eye symptoms were observed in 100% in vitamin D deficient (28.70 ± 4.49 nmol/l) participants (Kurtul et al, 2015a). Of our studied population, 1/3 with optimal vitamin D levels showed at least mild dry eye symptoms (OSDI > 12), while dry eye symptoms were observed in 50% of people with vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Jee et al (2016) reported no effect, whereas Yildirim et al (2016) and Kurtul (2015b) suggested good improvements. Jin et al (2016) observed that TBUT was shorter in people with vitamin D deficiency, but did not measure a significant impact on OSDI scores or fluorescein staining (Jin et al, 2016).…”
Section: Impact Of Vitamin D Supplements On Dry Eyementioning
confidence: 99%
See 1 more Smart Citation